2011
DOI: 10.1289/ehp.1003200
|View full text |Cite
|
Sign up to set email alerts
|

TRPA1 and Sympathetic Activation Contribute to Increased Risk of Triggered Cardiac Arrhythmias in Hypertensive Rats Exposed to Diesel Exhaust

Abstract: Background: Diesel exhaust (DE), which is emitted from on- and off-road sources, is a complex mixture of toxic gaseous and particulate components that leads to triggered adverse cardiovascular effects such as arrhythmias.Objective: We hypothesized that increased risk of triggered arrhythmias 1 day after DE exposure is mediated by airway sensory nerves bearing transient receptor potential (TRP) channels [e.g., transient receptor potential cation channel, member A1 (TRPA1)] that, when activated by noxious chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
111
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(124 citation statements)
references
References 38 publications
10
111
0
3
Order By: Relevance
“…Reductions in pulmonary function have also been reported following occupational exposures in chronic studies (Rudell et al, 1996). In addition, diesel PM has been associated with changes in heart rate, increased incidence of arrhythmias, impairment of vasodilation, increase in blood pressure, and systemic inflammation (Hazari et al, 2011;Peretz et al, 2008;Tornqvist et al, 2007;Nemmar et al, 2007;Carll et al, 2013;Harkema et al, 2009;Knuckles et al, 2011). Human studies by Mills et al (2005Mills et al ( , 2007aMills et al ( , 2007b) demonstrated a dose-dependent increase in prothrombotic effects and acute myocardial ischemia upon exposure to diesel exhaust.…”
mentioning
confidence: 98%
“…Reductions in pulmonary function have also been reported following occupational exposures in chronic studies (Rudell et al, 1996). In addition, diesel PM has been associated with changes in heart rate, increased incidence of arrhythmias, impairment of vasodilation, increase in blood pressure, and systemic inflammation (Hazari et al, 2011;Peretz et al, 2008;Tornqvist et al, 2007;Nemmar et al, 2007;Carll et al, 2013;Harkema et al, 2009;Knuckles et al, 2011). Human studies by Mills et al (2005Mills et al ( , 2007aMills et al ( , 2007b) demonstrated a dose-dependent increase in prothrombotic effects and acute myocardial ischemia upon exposure to diesel exhaust.…”
mentioning
confidence: 98%
“…It has been shown that components of urban PM, such as diesel exhaust PM (DEP), activate airway neurons that express transient receptor potential (TRP) ankyrin-1 (TRPA1) and TRP vanilloid-1 (TRPV1) (1)(2)(3)(4)(5)(6)(7)(8). TRPA1 and TRPV1 are members of the TRP family of ion channels.…”
mentioning
confidence: 99%
“…This family of receptors appears to function as environmental sensors and mediate protective responses in the respiratory tract that include stimulation of the cough reflex, suppression of respiratory drive, and the initiation of immune responses; TRPA1 and TRPV1 also trigger pulmonary edema via the release of substance P and neurokinin A (9). TRPA1 has also been implicated in cardiovascular dysfunction associated with pulmonary DEP exposure in rats (8). TRPA1 and TRPV1, as well as other TRP channels, are expressed by various airway epithelial and alveolar cells in addition to airway neurons.…”
mentioning
confidence: 99%
“…Abrogation of these cardiac effects by a selective TRPV1 antagonist capsazepine suggested that TRPV1-mediated autonomic reflexes play a central role therein (Ghelfi et al, 2008). In another study employing a gaseous pollutant (Hazari et al, 2011), one-day exposure of rats to diesel exhaust gas resulted in increased heart rate with pro-arrhythmic ECG changes of prolonged action potential and shorted repolarization. Notably, these rats showed much heightened sensitivity to aconitine challenge that can induce moderate to lethal ventricular tachyarrhythmias dose-dependently.…”
Section: Arrhythmia Related To Autonomic Imbalancementioning
confidence: 99%